Methomyl poisoning presenting with decorticate posture and cortical blindness - Chih-Ming Lin (MDPI AG, 2014)
Methomyl is a potent pesticide that is widely used in the field of agriculture. The systemic toxic effects of methomyl have been well described. However, the neurological effects of methomyl intoxication are not well understood. In this study, we report a 61-year-old Taiwanese man sent to our emergency department because of altered mental status. His family stated that he had consumed liquid methomyl in a suicide attempt. He was provided cardiopulmonary resuscitation because of unstable vital signs. He was then sent to an intensive care unit for close observation. On the second day of admission, he regained consciousness but exhibited irregular limb and torso posture. On the sixth day, he started to complain of blurred vision. An ophthalmologist was consulted but no obvious abnormalities could be identified. On suspicion of cerebral disease, a neurologist was consulted. Further examination revealed cortical blindness and decorticate posture. Cerebral magnetic resonance imaging (MRI) was arranged, which identified bilateral occipital regions lesions. The patient was administered normal saline and treated with aspirin and piracetam for 3 weeks in hospital. During the treatment period, his symptom of cortical blindness resolved, whereas his decorticate posture was refractory. Follow-up brain MRI results supported our clinical observations by indicating the disappearance of the bilateral occipital lesions and symmetrical putaminal high signal abnormalities. In this article, we briefly discuss the possible mechanisms underlying the cerebral effects of methomyl poisoning. Our study can provide clinicians with information on the manifestations of methomyl intoxication and an appropriate treatment direction.